Prospective Epidemiological Study of Basketball Injuries During One Competitive Season: Ankle Sprains and Overuse Knee Injuries - Cumps, Elke (Asist Group, 2007)
This prospective cohort study aims to assess the overall incidence of acute and overuse basketball injuries and identifies risk factors associated with ankle sprains and knee overuse injuries. In total, 164 senior players (23.7 years ± 7.0) of all levels of play, and including both men and women, participated voluntarily during one season. A total of 139 acute and 87 overuse injuries were reported, resulting in an overall injury incidence of 9.8 (8.5 to 11.1) per 1,000 hours. The incidence of acute injuries was 6.0/1,000 hours. Ankle sprains (n = 34) accounted for most acute injuries, and 52.9% of all players with ankle sprains reported a previous ankle sprain. Relative Risks (RR) and Odds Ratio (OR) with their 95% Confidence Intervals (CI) were calculated to determine significant differences. Landing on an opponent’s foot was the major inciting event, significantly more so than non contact mechanisms (RR=2.1 [95% CI: 1.0-4.2]). Acute knee injuries resulted in the highest playing absence (7 weeks 2 days ± 9 weeks 1 day). Overuse injury incidence was 3.8/1,000 hours. The knee (1.5/1,000 hours) was the most common site. Forward players sustained less knee overuse injuries than players of all other playing positions, and significantly less than center players (OR=0.5 [95% CI: 0.2-0.9]). This study showed that ankle sprains and overuse knee injuries are the most common injuries in basketball, both accounting for 14.8%. Injury prevention programmes however should not concentrate on those injuries only, but might one to consider that acute knee injuries, in spite of the fact that they occur less frequently, also merit further research.